Advances and challenges in anti-cancer vaccines for multiple myeloma - Abdollahi, Pegah; Norseth, Hanne Marie; Schjesvold, Fredrik (Frontiers in Immunology, 2024)
Multiple myeloma (MM) is a hematological cancer marked by plasma cell accumulation in the bone marrow. Despite treatment advancements, MM remains incurable in most patients. MM-associated immune dysregulation fosters disease progression, prompting research into immunotherapy to combat the disease. An area of immunotherapy investigation is the design of myeloma vaccine therapy to reverse tumor-associated immune suppression and elicit tumor-specific immune responses to effectively target MM cells. This article reviews vaccine immunotherapy for MM, categorizing findings by antigen type and delivery method. Antigens include idiotype (Id), tumor-associated (TAA), tumor-specific (TSA), and whole tumor lysate. Myeloma vaccination has so far shown limited clinical efficacy. However, further studies are essential to optimize various aspects, including antigen and patient selection, vaccine timing and sequencing, and rational combinations with emerging MM treatments.